Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f\colon \prod \mathbb{Z} \rightarrow \mathbb{Z}$ be a $\mathbb{Z}$-module homomorphism. I want to show that $f(e_i) = 0$ for almost all $i$ where $e_i$ are the standard unit vectors. I assume $f(e_i) \neq 0$ for infinitely many $i$. We can assume without restriction that $f(e_i) > 0$ for all $i \geq 1$. Now is the following a valid argument and if not why? It is $f(\sum e_i) = \sum (f(e_i)) = \infty$, a contradiction. Or do I have to use a trickier argument?

share|cite|improve this question
an homomorphism only commutes with finite sums. So $f(\sum e_i)$ exists, but it isn't related to $\sum f(e_i)$, and it doesn't imply that this sum should converge. I remember that this problem is quite tricky. – mercio Nov 25 '11 at 15:42
You should specify what your product is being taken over. – Dylan Moreland Nov 25 '11 at 17:06

Suppose $f : \prod \mathbb{Z} \to \mathbb{Z}$ is a group morphism. (I assume the product is indexed by $\mathbb{N}$.)

Let $(x)$ be a sequence of strictly positive numbers $(x_0, \ldots, x_n, \ldots)$ such that for all $n\ge 0$, $x_n > 2 |f(x_0, \ldots, x_{n-1}, 0, \ldots)|$ and for all $n \ge 1$, $x_n$ is a multiple of $x_{n-1}$ strictly larger than $x_{n-1}$.

Now, $(x_n)$ is increasing, so there exists $n_0$ such that $x_{n_0} > 2 |f(x)|$. Suppose $n\ge n_0$

$f(x) - f(x_0, \ldots, x_{n-1}, 0, \ldots) = f(0, \ldots, 0, x_n, \ldots) \equiv 0 \pmod {x_n}$ But $|f(x) - f(x_0, \ldots, x_{n-1}, 0, \ldots)| \le |f(x)| + |f(x_0, \ldots, x_{n-1}, 0, \ldots)| \lt x_n/2 + x_{n_0}/2 \le x_n$.

A number which is a multiple of something strictly bigger than itself has to be zero, so $f(x) = f(x_0, \ldots, x_{n-1}, 0, \ldots)$ for all $n \ge n_0$.

In particular, for all $n\ge n_0$, $f(x_n e_n) = f(x)-f(x) = 0$, and since $x_n > 0$, $f(e_n) = 0$

A similar trick can show that in fact, $f(x) = \sum_{k=0}^{n_0} x_k f(e_k)$ for all sequences $(x)$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.